SOASPE: a Framework for the Performance Analysis of Service Oriented Software - Holanda, Henrique Jorge; Barroso, Giovvani Cordeiro; Serra, A. B. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2009: Anais do V Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2009.6178, 2009)
Business Process Execution Language for Web Services (BPEL4WS) is a promising language describing the Service Oriented Software (SOS) orchestrations in form of Business Processes, but it lacks of a sound formal semantic, which hinders the formal analysis and verification of business processes specified in it. Formal methods, like Petri Nets (PN), may provide a means to analyse BPEL4WS processes, evaluatingits performance, detecting weaknesses and errors in the process model already at design-time. This paper addresses quality of SOS orchestrations created using the BPEL4WS and a framework for transformation of BPEL4WS into Generalized Stochastic Petri Nets (GSPN) is proposed to analise the performance and throughput of SOS, based on the execution of orchestrated processes.